THE EFFECTIVENESS OF USING ROLE PLAY METHOD TO IMPROVE THE SPEAKING SKILLS OF CHILDREN AGED 7-10 AS EFL STUDENTS AT EBISIE ENGLISH COURSE - Anak Agung Ayu Mas Sukmawati; I Gusti Ayu Lokita Purnamika Utami; Made Hery Santosa; Ni Made Ratminigsih (Jurnal Santiaji Pendidikan (JSP), 2025)
This study investigates the efficacy of the role-playing method in improving speaking skills in children who are studying English as a foreign language (EFL) at Ebisie English Course and range in age from 7 to 10. This study aims to find out how well role play helps young EFL students in developing speaking skills, how role-play activities impact students' motivation to use English, and whether there are any challenges that might prevent role play from being used successfully in the classroom. The study uses a qualitative methodology, evaluating the effect of role play on motivation and speaking skills through observations and both teachers and students’ opinions. According to research, role play greatly improves students' speaking abilities by creating a lively and attractive learning environment that also increases intrinsic motivation. In addition to improving language learning, role play also encourages social interaction and minimizes levels of stress in learners, according to the discussion of the data. This study offers a conceptual and empirical contribution by highlighting the importance of active learning methods in learning a language and providing examples of successful teaching methods for young EFL students.